Cu particle seeded InP–InAs axial nanowire heterostructures. Issue 10 (23rd July 2013) - Hillerich, Karla; Ghidini, Dario S.; Dick, Kimberly A.; Deppert, Knut; Johansson, Jonas
Abstract <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text> We demonstrate the epitaxial growth of alternating InP–InAs nanowire heterostructures using Cu seed particles in MOVPE. We observe extraordinary early stages in the formation of InAs segments, e.g. three‐dimensional nucleation instead of step‐flow growth. Furthermore, InAs segments of thin nanowires exhibit extended 4H crystal structure. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text> Color coded XEDS elemental map of a typical InP–InAs nanowire heterostructure seeded by a Cu particle. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)